A study on the perception of Filipinos on instafood photos and the reasons behind foodstagramming - Ang, Jomarie W.
ABSTRACT Foodstagramming is defined to be the activity of taking an image or a photograph of food and posting it on the internet via the social media. Even though the act of documenting food dates back to the olden times, foodstagramming is currently considered as a trend as it is being done by the young and the young at heart. This exploratory research study aims to determine the factors, perceptions, and motivations of people on foodstagramming through the collection of primary data in the form of surveys. From the sixty-six respondents, it was observed that age and gender are key players in determining whether a person is a foodstagrammer or not. From the data gathered, it was interpreted that there is a significant relationship between being a foodstagrammer and age, as well as being a foodstagrammer and gender. Most of the foodstagrammer are women and belonging to the 20-29 years old range. Moreover, it was found out that having a smartphone and having accounts in social media website Twitter and Instagram have a significant relationship in being a foodstagrammer. It was learned from the data gathered and collected that the motivation behind a foodstagrammer to take and post food photos online is because of the reason of showing off to social media friends, and the reason of wanting to document food eaten. Both foodstagrammers and non-foodstagrammers will be likely to take and post food photos given that it is visually and aesthetically pleasing. Moreover, doing the act of foodstagramming possess its own benefits just like getting praises from friends and people, which is also just along the line of wanting to showoff to friends. Ang, Baron & Tagud. It was concluded that even though there has been a significant relationship between the demographic profiles of respondents such as age and gender, it can still be said that foodstagramming is an activity that doesn‟t just apply to the youth or the ladies. It is an activity that is done by a lot of people nowadays, whether they are in their 20s or 40s, or whether the person is a man or a woman. This study is just a base line for more related studies in the fields of the arts, food, and business. Hopefully, more studies can spring off from this research study that can help shape the future conditions of the industry. The group recommends that an in-depth study be done where more respondents will participate for the primary data collection. In this case, the study being done will have a firmer grip on accuracy and precision, and more insights will be learned from them. Ultimately, since this study can be related to other fields like social media marketing, the group thinks that a further study be made in relation with new age marketing, such as the use of social media.